2016
DOI: 10.12720/joace.4.2.96-103
|View full text |Cite
|
Sign up to set email alerts
|

A Control Strategy based on Fuzzy Logic for Three-phase Grid-connected Photovoltaic System with Supporting Grid-frequency Regulation

Abstract: This paper presents a control strategy based on fuzzy logic to inject efficiently the active power from a three-phase grid-connected photovoltaic (PV) system into the local grid with supporting regulation for the frequency of grid voltage. In which the control strategy consists of three main modules as follows. Firstly, a simulation module based on the mathematical model of a PV panel is utilized to predict the maximum total power from PV arrays; the second one is a frequency regulation module used to compute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In [13], a prior study by the present two authors showed a simple single-level control method suitable for a small PV power agent, but no coordinated control strategy was proposed for a large-scale PV farm. In addition, the tolerable range of grid frequency deviation at the steady state used in [13] was ±0.075 (Hz), which is 50% larger than the often-used range of ±0.05 (Hz). A coordinated strategy for PV farms was presented initially in [14].…”
Section: Introductionmentioning
confidence: 93%
“…In [13], a prior study by the present two authors showed a simple single-level control method suitable for a small PV power agent, but no coordinated control strategy was proposed for a large-scale PV farm. In addition, the tolerable range of grid frequency deviation at the steady state used in [13] was ±0.075 (Hz), which is 50% larger than the often-used range of ±0.05 (Hz). A coordinated strategy for PV farms was presented initially in [14].…”
Section: Introductionmentioning
confidence: 93%
“…In every nation, DERs, ESS, and the main grid should work inside adequate emission limits subject to the emission standards reference guide to improve the open picture. The emission, such as CO 2 (carbon dioxide), SO 2 (sulfur dioxide) and NO x (nitrogen oxides)are considered in this work . For every gas in kg at hour t , every unit ought not to surpass the most extreme noteworthy emission rate.…”
Section: Distributed Energy Management For Hybrid Mg Systemmentioning
confidence: 99%
“…The emission, such as CO 2 (carbon dioxide), SO 2 (sulfur dioxide) and NO x (nitrogen oxides)are considered in this work. 33 For every gas in kg at hour t, every unit ought not to surpass the most extreme noteworthy emission rate. From electrical power generation at MG and the utility grid, the air emissions are directed by these structured constraints, which can be formulated in the accompanying equations:…”
Section: Emission Constraintmentioning
confidence: 99%
“…In the case of grid-connected PV system, different inverter topologies and controllers are usually used for interfacing the PV array and the utility grid [12][13][14]. Two inverter configurations and three inverter topologies can be identified in such applications, namely: central inverter, string inverter and integrated inverter for configuration; and topologies with or without transformer [12].…”
Section: Inverter Modeling and Control System 231 Inverter Modelingmentioning
confidence: 99%